Analysis of carrier injection efficiency of AlGaN UV-B laser diodes based on the relationship between threshold current density and cavity length. (14th June 2021) - Sato, Kosuke; Omori, Tomoya; Yamada, Kazuki; Tanaka, Shunya; Ishizuka, Sayaka; Teramura, Shohei; Iwayama, Sho; Iwaya, Motoaki; Miyake, Hideto; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu
Abstract: The carrier injection efficiency η i of recently developed UV-B laser diodes (LDs) is estimated on the basis of fundamental calculations and measurements. A general procedure to estimate η i based on the relationship between the differential external quantum efficiency and the cavity length proves to be inadequate because of the large variation. To estimate η i without relying on the unstable output power, we analyze in detail how the threshold current density relates to the cavity length. By applying a light confinement factor of 3.5%, an internal loss of 10 cm −1, a current density of 0.56 kA cm −2 in the emission layers at zero gain, and a reflectivity of the mirror facet of 0.16, we estimate η i ≈ 3.5% for UV-B LDs. This low η i in UV-B LDs is due to unbalanced injection between electron and hole currents, which leads to electron overflow to the p-GaN side, as indicated by a simulation.